Impact of Yeast Diet on the Number of Eggs and Larvae Produced in Honey Bee Colonies (Apis Mellifera L.) Apidae: Hymenoptera - Hafiz Khurram Shurjeel; Muhammad Anjum Aqueel; Arooba Rubab; Shazia Iqbal; Ambreen Akram; Nadia Saeed (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
Honey bees (Apis mellifera L.) are important social insects because of the honey production and pollination services they provide. Diet quality affects bee progression through different life stages, adult longevity, fecundity and foraging activity, among other likely phenotypes. This study was conducted to determine the probable effect of colony food availability on the number of eggs and resulting larvae produced by honey bee colonies. Sixteen honey bee hives were used in the study. The hives were split into groups of four, with each group receiving one of the following four treatment diets: (1) T1 – sugar water (1 l water + 250 g sugar), (2) T2 - yeast water (1 l water and 50 g Brewer’s yeast‒ non-floral protein diet in dry form), (3) T3 – water (1 l water), and (4) T4 – no diet. The impact of the colony diet (sugar syrup and yeast with treatments mentioned above) on the number of eggs and larvae produced was determined using a one-way ANOVA conducted using the statistical program “R” version 2.15.3. Where appropriate, means were compared using the least significant difference (LSD). Numerically, the average number of eggs and larvae on sugar solution were 24.20 ± 1.72 and 26.8 ± 1.808 respectively, while on the yeast diet were 33.66 ± 2.92 and 31.55 ± 2.324, respectively. Significantly, the number of eggs (P-value 4.74E-10, F value 21.50528 and F-tabulated value as 2.731807) and larvae (P-value 5.31E-05, F-value 8.70 and F-tabulated value 2.73) produced was significant when colonies were fed with yeast and sugar solution.